21ST Century Characteristics of Educators as Perceived by Laguna State Polytechnic University Faculty - Buenvinida, Lerma P.; Rodriguez, Maria Teresa M.; Sapin, Sherwin B. (Advances in Social Sciences Research Journal, 2020)
This descriptive research aimed to determine the level of perception of faculty of Laguna State Polytechnic University on the 21st century characteristics of educator. Demographic profile of the respondent includes age, sex, status, educational attainment, academic rank, and years of service. The study identified six characteristics of 21st century educators such as adaptor, lifelong learner, technology savvy, collaborator, visionary, and leader. It was found out that the highest computed mean and standard deviation of 5.59 (0.13) was obtained from collaborator as one of the characteristics of educator and was interpreted as strongly agree. The faculty have developed and enhanced their knowledge and skills in teaching in order to adopt with the demands of 21st century learners. It is suggested that faculty members should continue to enhance their 21st century skills such as developing and applying new pedagogies in teaching and learning; and implementing design thinking and system thinking for educators.